Can supplier innovations substitute for internal R&D? A multiple case study from an absorptive capacity perspective. Issue 4 (October 2017) - Pihlajamaa, Matti; Kaipia, Riikka; Säilä, Julius; Tanskanen, Kari
Abstract: Prior literature suggests that significant internal R&D resources are needed to leverage suppliers for innovation and that external knowledge sources can be used to complement the internal knowledge base. Based on the analysis of four inbound open innovation projects at Fortum, a multinational energy utility company, we argue that companies with low R&D intensity may adopt an alternative approach which aims at substituting – not merely complementing – internal R&D with external innovations. We adopt the absorptive capacity perspective while investigating the cases and focus on four distinct capabilities: acquisition, assimilation, transformation, and exploitation. We find that the substitution approach consists of short-term research on new technological areas in order to gain the ability to identify and evaluate alternative technologies, as well as joint business models and operations based on complementary capabilities between the parties. The cases also suggest that the innovation process requires significant collaboration and the buying company's supplier management capabilities may improve the success of inbound open innovation projects of this type. Highlights: We adopt absorptive capacity perspective to study supplier innovations in a low R&D intensity context. The buyer firm can substitute internal R&D with supplier innovations. The buyer firm may exploit a supplier's knowledge without assimilating it. The acquisition, transformation, and exploitation of supplier innovations benefit from supplier management capabilities.